Influence of Ti-Base-Supported Implant Restoration on Peri-implant Conditions: A Systematic Review and Meta-analysis. - Han-Pang Liu; Sieu Yien Chiam; Hom-Lay Wang (International Journal of Oral & Maxillofacial Implants)
Purpose: To conduct a systematic review and meta-analysis to examine the impact of titanium (Ti) base-supported single-implant restorations on peri-implant conditions. Materials and Methods: Six randomized controlled trials (RCTs) comprising 274 implants met the inclusion criteria and were chosen for data analysis. A random-effects model was employed for the meta-analysis. Results: Data from this study revealed that the Ti-base group exhibited a small but statistically significant increase in peri-implant marginal bone loss (MBL; mean difference = 0.088 mm; 95% CI = 0.003 to 0.17; P = .041) compared to the one-piece abutment group. These effects were consistent in the subgroup analysis of regularly threaded implants compared to the microthreaded subgroup. No significant differences were observed between the Ti-base group and the abutment group concerning probing depth (PD), bleeding on probing (BoP), and the risk of prosthetic-related complications. Conclusions: The use of a Ti-base in a single implant-supported restoration is associated with a slight increase in peri-implant MBL, while other peri-implant health parameters show no significant correlation. Therefore, the evidence of the impact that Ti-bases have on the peri-implant conditions of single implant-supported restorations is insufficient based on the findings of the present meta-analysis.